32. Facio-brachial dystonic seizures in LGI1 Limbic Encephalitis: Analysis of video EEG monitoring in a small group of patients. Issue 12 (December 2017) - Cesnik, E.; Fallica, E.; Mazzoli, S.; Rispoli, V.; Govoni, V.; Calanca, C.; Tugnoli, V.
Abstract : Leucine-rich glioma inactivated 1(LGI1) antibodies are frequently associated with a common form of limbic encephalitis (LE) presenting with cognitive impairment, tonic-clonic and distinctive facio-brachial dystonic seizures (FBDS), not related with a specific EEG pattern. We describe clinical-EEG features of three patients with LGl1-LE with different response to immunotherapy. Three pts, admitted to our Neurology department for LE with positive test for LGI1 antibodies, performed video-EEG monitoring and immunotherapy. Video and still images showed frequently (3–40 episodes/day) paroxysmal brief events characterized by facial grimacing and sometimes dystonic arm posturing, with alternating side, suggestive for FBDS. We observed electrodecremental events (EDEs) or a contralateral slow-wave before "dystonic seizures" but not a clear ictal-EEG pattern. In all of the patients interictal EEG was normal. Furthermore, Video-EEG monitoring revealed multiple daily electrographic temporal seizures. Immunotherapy were associated with control of FBDS in two of three presented patients, with different latency. Video-EEG monitoring of our LGI1-LE patients showed frequent FBDS and bilateral temporal seizures. The lack of a clear ictal-EEG pattern for FBDS and the positive response to immunotherapy, support the hypothesis that dystonic episodes does not have a cortical origin, but are rather related to a possible basal ganglionic dysfunction.